An Analysis of the Influence of Digital Media Literacy and Students’ Learning Activities on Learning Outcomes in Islamic Religious Education at SMK Mahyal Ulum Al-Aziziyah - Zahriana (Wasatha: Jurnal Studi Islam dan Humaniora, 2026)
The rapid development of digital technology has transformed educational paradigms toward digital media literacy–based learning, which requires critical, collaborative, and creative thinking skills. This study aims to analyze the influence of digital media literacy and students’ learning activities on Islamic Religious Education (PAI) learning outcomes at SMK Mahyal Ulum Al-Aziziyah, Aceh Besar. Employing a quantitative approach with a correlational design, the study involved all 11th-grade students as the research population, selected through proportionate stratified random sampling. Data were collected using questionnaires, observations, and documentation, and analyzed through multiple regression tests. The results indicate that digital media literacy has a positive and significant influence on PAI learning outcomes, suggesting that the better students utilize digital media, the higher their learning achievement. Furthermore, learning activities significantly affect students’ academic performance. Simultaneously, both digital media literacy and learning activities contribute meaningfully to improving PAI learning outcomes. These findings highlight the importance of integrating digital literacy and active learning as pedagogical strategies to enhance the quality of Islamic religious education in the era of Industrial Revolution 4.0.